2018
DOI: 10.1038/s41598-018-31201-2
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Joule heating and spin-orbit torques in the direct current induced magnetization reversal

Abstract: Current-induced magnetization reversal via spin-orbit torques (SOTs) has been intensively studied in heavy-metal/ferromagnetic-metal/oxide heterostructures due to its promising application in low-energy consumption logic and memory devices. Here, we systematically study the function of Joule heating and SOTs in the current-induced magnetization reversal using Pt/Co/SmOx and Pt/Co/AlOx structures with different perpendicular magnetic anisotropies (PMAs). The SOT-induced effective fields, anisotropy field, switc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 59 publications
(54 reference statements)
0
26
0
Order By: Relevance
“…[ 31 ] Thus, not only the magnetization but also the exchange‐bias are reversed by SOT. Due to the deterministic magnetization switching by SOT, [ 11–13,26–30 ] only the up (down) magnetized domain could be switched to opposite direction under a positive (negative) current pulse with an assistance field of + H x , as schematically shown in Figure 1e,f. Thereby, concurrent switching of FM magnetization and AFM interfacial spins by SOT can be realized.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 31 ] Thus, not only the magnetization but also the exchange‐bias are reversed by SOT. Due to the deterministic magnetization switching by SOT, [ 11–13,26–30 ] only the up (down) magnetized domain could be switched to opposite direction under a positive (negative) current pulse with an assistance field of + H x , as schematically shown in Figure 1e,f. Thereby, concurrent switching of FM magnetization and AFM interfacial spins by SOT can be realized.…”
Section: Resultsmentioning
confidence: 99%
“…The SOT effect has been demonstrated as an efficient way to switch the magnetization of FM or AFM, and was widely investigated owing to its potential applications in magnetic random access memory (MRAM) and other spintronic devices. [ 11–13,26–30 ] In particular, in HM/FM/AFM trilayers, Lin et al recently reported that the hysteresis loops between positively and negatively single‐biased loops could be manipulated by SOT through switching the FM spins and AFM interfacial spins completely and simultaneously with magneto–optical Kerr techniques. [ 31 ] It provides an effective approach to manipulate the FM magnetization and AFM interfacial spins in HM/FM/AFM trilayers by SOT.…”
Section: Introductionmentioning
confidence: 99%
“…Such spin-dynamics simulations could clarify as well the role of the non-staggered, homogeneous components for the switching and the influence of Joule heating, inherently present in all experiments. It was shown recently that Joule heating plays an essential role as it drastically decreases the required switching field and enhances the spin–orbit torque efficiency 49 . Also for MnAu, it was lately concluded that Joule heating can provide a sufficient thermal activation for switching processes 31 .…”
Section: Discussionmentioning
confidence: 99%
“…Thermal effects in currentinduced spin-orbit torque switching have been extensively studied in the literature and it was shown that it can lead to a reduced value of the in-plane field necessary to initially break the system symmetry or induce a crossing of the compensation point in synthetic ferrimagnets. [34][35][36] The emergence of an intermediate resistance state when sweeping the current was observed in the SOT switching experiments for certain CoGd structures. As seen in Figure 2c for Pt/Co 73 Gd 27 /W, an intermediate resistance plateau appeared in the current switching hysteresis loops at low in-plane magnetic field.…”
Section: Spin-orbit Torque Switchingmentioning
confidence: 99%